2021
DOI: 10.3390/cells10092386
|View full text |Cite
|
Sign up to set email alerts
|

The Pathogenic and Therapeutic Implications of Ceramide Abnormalities in Atopic Dermatitis

Abstract: Ceramides play an essential role in forming a permeability barrier in the skin. Atopic dermatitis (AD) is a common chronic skin disease associated with skin barrier dysfunction and immunological abnormalities. In patients with AD, the amount and composition of ceramides in the stratum corneum are altered. This suggests that ceramide abnormalities are involved in the pathogenesis of AD. The mechanism underlying lipid abnormalities in AD has not yet been fully elucidated, but the involvement of Th2 and Th1 cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 117 publications
0
20
0
Order By: Relevance
“…The bent structure of the acyl chain due to the cis double bond is suggested to decrease the packing density of the lipid bilayer and weaken the lipid–lipid interaction [ 53 ]. While the relevance of this particular sphingoid base in AD still requires further study, altered sphingoid base profiles have been observed in relation to skin barrier abnormality in AD [ 55 , 56 ]. Our results point toward a possible role of FADS3 in AD etiology, with myristic acid representing a potential novel target for personalized preventive approaches.…”
Section: Discussionmentioning
confidence: 99%
“…The bent structure of the acyl chain due to the cis double bond is suggested to decrease the packing density of the lipid bilayer and weaken the lipid–lipid interaction [ 53 ]. While the relevance of this particular sphingoid base in AD still requires further study, altered sphingoid base profiles have been observed in relation to skin barrier abnormality in AD [ 55 , 56 ]. Our results point toward a possible role of FADS3 in AD etiology, with myristic acid representing a potential novel target for personalized preventive approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the AD lipid research has focused on the ceramides abnormalities 49 and led to development of numerous ceramide-containing moisturizers, with the assumption they would improve dry skin and barrier function. 74 There is a real need for randomized double blind placebo control studies of these products to evaluate their effect on skin barrier function and AD clinical improvement.…”
Section: What Is Known About Epidermal Abnormality In Ad?mentioning
confidence: 99%
“…Recently, there has been considerable interest in a subtype of sphingolipids known as ceramides, and in particular ceramide level derangements in skin and metabolic health. While the pleiotropic effects of ceramides have been reviewed extensively [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ], knowledge of its abundance in relation to intracellular lipid partitioning and regulation remains patchy. This review starts with a summary on the significance of ceramides in well-studied areas such as skin abnormalities and metabolic disease, before a focus on current knowledge surrounding intracellular lipid regulation and its relation to intracellular ceramide levels.…”
Section: Introductionmentioning
confidence: 99%